Pendekatan Interaktif dalam Edukasi Menabung untuk Meningkatkan Literasi Keuangan Siswa di SB Kampung Bharu Malaysia - Lelani, Siska; Firdaus, Firdaus; Hartono, Joko Setyo; Zahro, Aimatuz (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This study aims to determine how effective the savings education program is for primary school students in SB Kampung Bharu, Kuala Lumpur, Malaysia. The program involved students from grade 1 to grade 6, to introduce the concept of money and the importance of saving early on. The methods used in this activity include material provision, discussion, and hands-on practice. Educational activities include the introduction of currency, symbols, and heroes on rupiah money, as well as education on how to save and protect money. Students were also taught about the importance of saving money through interactive discussions and practice making piggy banks from used materials. The results showed that students had an increased understanding of various aspects of finance, including the value of money, the history behind the symbols on currency, and the importance of keeping their money safe. Discussions about saving money succeeded in instilling positive habits and an understanding of the importance of having spare money for urgent needs or long-term goals. The practice of making piggy banks not only enhanced students' creativity but also strengthened their understanding of the concept of saving money.